2015
DOI: 10.1007/s11095-015-1714-2
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhetinic Acid-Mediated Polymeric Drug Delivery Targeting the Acidic Microenvironment of Hepatocellular Carcinoma

Abstract: This novel GA-PPP polymeric carrier is promising for targeted treatment of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…To design a delivery system with active targeting and efficient stimuli-responsiveness has been promising. 40 BMP-2 is a member of the TGF-β superfamily of proteins and involved in abundant biological actions. 15 However, its poor bioavailability by fast clearance, poor permeability and Ki-67 expression, expressed as the mean ± SD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To design a delivery system with active targeting and efficient stimuli-responsiveness has been promising. 40 BMP-2 is a member of the TGF-β superfamily of proteins and involved in abundant biological actions. 15 However, its poor bioavailability by fast clearance, poor permeability and Ki-67 expression, expressed as the mean ± SD.…”
Section: Discussionmentioning
confidence: 99%
“…39 Many studies have shown that the target site of GA is expressed highly in hepatoma carcinoma cells than the nontumor hepatocytes, and GA can be combined with functionalized hepatoma carcinoma cell-targeting drug carrier, including PIC micelle, to enhance the anti-hepatoma carcinoma cell properties as a ligand. 40,41 In this paper, we report GA-poly(ethylene glycol) (PEG)-b-poly(L-lysine) (PLL) as a potential BMP-2 carrier. The designed GA-PEG-b-PLL was composed of GA-PEG and PLL (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported the delivery of miR-221 antisense oligonucleotide (anti-miR-221) using negatively charged liposomes with transfer-rin (Tf) as a targeting ligand in in vitro and also in HepG2 tumor-bearing xenograft mice (Zhang, Peng, et al, 2015). …”
Section: Current Treatment Modalities For Hepatocellular Carcinomamentioning
confidence: 99%
“…GA-modified liposomal formulations of oxaliplatin, calcein, docetaxel, wogonin and also pDNA were discussed for effective targeted therapy for HCC. Zhang and colleagues studied poly (L-Histidine) (PHIS) mediated polymeric system (GA-PEG-PHIS-PLGA) with GA for targeted delivery of the anti-cancer agent andrographolide (Zhang, Zhang, et al, 2015). …”
Section: Nanomedicines and Drug Delivery For Treating Hepatocellulmentioning
confidence: 99%
“…23 MCF-7/ ADR cells were cultured at a density of 5×10 3 cells/well in six-well plates for 24 h. The cells were treated with MIT and MIT-PFP/PPP mixed micelles and irradiated with a laser as mentioned above. After incubation for 24 h at 37°C, the cells were collected by trypsinization, washed twice with ice-cold PBS and gently suspended in 100 μL binding buffer containing 20 μg/mL Annexin V-fluorescein isothiocyanate stain for 30 min, followed by staining with PI (10 μL) for 5 min.…”
Section: Assessment Of Cell Apoptosismentioning
confidence: 99%